Maximizing the efficiency of resistance training - Pawlina, Mateusz; Ziętara, Karolina; Raksa, Karolina; Nowakowska, Katarzyna; Lewkowicz, Martyna (Journal of Education, Health and Sport, 2022)
Introduction and objective: Resistance training is the main intervention that can develop an individual’s strength and muscle mass. When executed regularly, it provides significant health benefits. The aim of this study is to analyze the current level of knowledge on maximizing the efficiency of resistance training in the context of muscle hypertrophy and increase in muscle strength. Materials and methods: PubMed and Google Scholar databases were searched. The criteria for qualifying the article for the review were the following keywords: hypertrophy, resistance training, muscle strength, and efficiency. 10 articles from 2017 to 2022 were analyzed. Description of the state of knowledge: To optimize the way of performing RT, its assumptions should be individually adapted to the exercising person. In the conventional model of muscle hypertrophy, three main factors are distinguished: muscle tension, metabolic stress, and muscle damage. Maintaining greater mechanical muscle tension during training primarily promotes an increase in its strength while increasing metabolic stress is responsible for the intensification of hypertrophy. In terms of hypertrophy, it has been observed that more series of exercises per week means greater gains in muscle mass. Multi-joint exercises involve more muscle mass than single-joint exercises. Summary: To control the effectiveness of training 1RM should be measured before and after the training cycle. Performing exercises with a high load (RM ≤7) may be the most effective training method for people with limited time resources. To maximize the efficiency of training, only multi-joint exercises may be used.